1978
DOI: 10.1002/1097-4679(197807)34:3<633::aid-jclp2270340310>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in birth patterns of schizophrenics

Abstract: Birth patterns of non-aboriginal, first admission, Western Australian psychiatric patients born between 1920 and 1950 were compared statistically with those of the general population. Three I. C. D. categories were examined: schizophrenia, anxiety neurosis, and depressive neurosis. For both categories of neurosis no deviations from normal birth patterns were observed. For males, marked excesses in schizophrenic births were observed in June, and for females a similar excess occurred in September. Possible expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The seasonality of birth in alcoholics has only sporadically been studied. In a recent review on seasonality of birth, alcoholism was not mentioned (7), and also, in many studies including different diag-nostic groups alcoholism was not considered (8,11,13,(15)(16)(17). In a large group including alcohol psychosis, alcoholism and drug abuse, Dalen (3) found no significant seasonal trend, and similar results were reported by Lang (2) and Watson et al (14).…”
mentioning
confidence: 66%
“…The seasonality of birth in alcoholics has only sporadically been studied. In a recent review on seasonality of birth, alcoholism was not mentioned (7), and also, in many studies including different diag-nostic groups alcoholism was not considered (8,11,13,(15)(16)(17). In a large group including alcohol psychosis, alcoholism and drug abuse, Dalen (3) found no significant seasonal trend, and similar results were reported by Lang (2) and Watson et al (14).…”
mentioning
confidence: 66%
“…Berk et al (19) reported excesses in November, December and January, in line with northern hemisphere trends for months but representing opposite seasons. While four of the 10 studies that analysed seasonality data separately by sex found signi®cant excesses around the winter/spring months, neither sex predominated in the ®ndings; the excess was for females only in one study (20), for males only in another (21), and for both males and females in the other two studies (18,22). Several studies, including some that had found no overall excess, subdivided their samples into 10-or 5-year bands (some further subdivided their data by sex and/or hospital duration) and found some signi®cant winter/ spring excesses but for differing years (20,21,23).…”
Section: Southern Hemisphere Studiesmentioning
confidence: 99%
“…While most studies in the Northern Hemisphere demonstrate concordant results (Boyd et al, 1986; Bradbury and Miller, 1985; Davies et al, 2003; Gallagher et al, 2007; Machón et al, 1983; Pallast et al, 1994; Torrey et al, 1996), studies examining the association between winter birth and schizophrenia in the Southern Hemisphere are less robust. Several reports of the southern hemisphere have found a positive association between birth during the winter months and an increased risk of schizophrenia (Morgan et al, 2001; Syme and Illingworth, 1978). Other reports have found associations between risk of schizophrenia and birth during peak rainfall season in Northeast Brazil (de Messias et al, 2001, 2006), late spring and summer births (Berk et al, 1996), as well as an increased risk of avolition and apathy in schizophrenic patients born during the autumn and winter months in Africa (Jordaan et al, 2006).…”
Section: Epidemiologymentioning
confidence: 99%